Really wild animals Totally tropical rain forest. - Moore, Dudley (Washington, D.C. : National Geographic Video, 2005)
An animated globe named "Spin" shows viewers the variety of animals in the rain forest, including jaguars, frogs, and monkeys.
Narrator: Dudley Moore.
DVD.
Closed-captioned.
Keywords: Rain forest animals; Jaguar -- Behavior; Frogs -- Behavior; Monkeys -- Behavior; Video recordings for hard of hearing people; Animal films